In vitro analysis of the influence of the thermocycling and the applied force on orthodontic clear aligners - Cintora-López, Patricia; Arrieta-Blanco, Patricia; Martin-Vacas, Andrea; Paz-Cortés, Marta Macarena; Gil, Javier; Aragoneses, Juan Manuel (Frontiers in Bioengineering and Biotechnology, 2023)
The mechanical properties of polyurethane dental aligners have been studied in an oral environment at 37ºC and subjected to thermal cycling between 5 and 55ºC for long periods of time at different mechanical stresses. The aim is to determine the efficacy of the orthodontic aligner at different stress levels, the effect of thermal cycling with therapy time on tooth position correction. Sixty aligners with the same design were studied applying tensions of 0, 3 and 30N and determining the deformation at different times from 1 to 760 hours. Half of these aligners were subjected to stresses submerged in artificial saliva at 37ºC and the other half were subjected to thermal cycles between 2 and 55ºC in salivary medium. Deformation was determined using a high-resolution stereo magnifier and Image J image analysis software. Water adsorption by the polyurethane was determined at the different test times. The results showed that in the unloaded aligners there is no appreciable deformation, but with thermal cycling there is a light shrinkage of the aligner due to the semi-crystallization process (ordering of polymeric chains) of the polyurethane. When applying loads of 3 and 30N, creep curves with constant deformation transition zones can be seen. The transition zones decrease as the applied mechanical load increases. In addition, the significant effect of thermal cycling on the reduction of the transition zone of the aligners has been demonstrated. The transition zones are optimal for dental correction as constant stresses are exerted for tooth movement. The effect of thermal cycling shortens the constant deformation zone and reduces tooth alignment time. It was observed that the absorption of water in the aligner is constant after 1 hour of immersion and does not exceed 0.4% by weight of absorbed water.